OPTIMIZATION OF TREATMENT TACTICS IN PATIENTS WITH BENIGN PROSTATIC HYPERPLASIA ACCORDING TO MORPHOLOGICAL CHANGES OF THE URINARY BLADDER WALL - Sarychev, L.P.; Starchenko, I.I.; Savchenko, R.B.; Sarychev, Y.V.; Pustovoyt, G.L. (World of Medicine and Biology, 2021)
60 patients with benign prostatic hyperplasia were divided into three groups according to their clinical manifestations – compensation, subcompensation and decompensation of the urinary bladder. According to the histological examination, prolonged bladder outlet obstruction leading to progressive destructive changes in smooth muscle cells, a decrease in the specific volume of muscle tissue and a decrease in the diameter of myocytes. Urothelium damage is accompanied by a loss of the barrier function, which results in sclerotic process. Substantiation of treatment tactics in patients with benign prostatic hyperplasia should be carried out taking into account the probable morphological changes in the bladder. Untimely elimination of the obstructive component leads to a loss of detrusor contractility. The therapeutic strategy for restoring detrusor contractility is to eliminate microcirculatory disorders and correct disorders of bioenergetic processes.
Keywords: benign prostatic hyperplasia; decompensated urinary bladder; metabolism-corrective therapy; anticholinesterase therapy